Implementation of the Inmate Rehabilitation Assessment System (SPPN) to Reduce Recidivism at the Class I Cipinang Prison in East Jakarta - Audyshia Rifa Charisma Sakti; Iqrak Sulhin (Green Publisher Indonesia, 2026)
This study examines the implementation of the Inmate Rehabilitation Assessment System (SPPN) in reducing recidivism at Class I Cipinang Prison, East Jakarta. The background of this research is rooted in the persistent issue of high recidivism rates in Indonesia, indicating that correctional institutions have not fully achieved their rehabilitative goals. The study aims to analyze how SPPN is implemented and to evaluate its effectiveness in shaping inmates’ behavior and preventing repeat offenses. This research employed a qualitative descriptive approach, involving purposive sampling of correctional officers and relevant stakeholders. Data were collected through in-depth interviews, direct observation, and documentation review, and analyzed using data reduction, data display, and conclusion drawing supported by qualitative analysis software. The findings reveal that SPPN plays a significant role in fostering behavioral change and moral awareness among inmates through structured programs, emotional approaches, and psychosocial interventions. However, its effectiveness is constrained by structural challenges such as overcapacity, limited human resources, and weak inter-agency coordination. Additionally, external factors, including social stigma and lack of post-release support, contribute to the persistence of recidivism. In conclusion, while SPPN is effective in promoting internal behavioral transformation during incarceration, it has not fully succeeded in reducing recidivism. Strengthening institutional capacity, enhancing cross-sector collaboration, and improving post-release support systems are essential to achieve sustainable rehabilitation outcomes.